Political Competition and Violence in Mexico: Hierarchical Social Control in Local Patronage Structures - Villarreal, Andres (American Sociological Review, 2002)
Many countries that have recently undergone transitions to democracy have experienced increases in violent crime. Yet sociological theories have generally failed to consider the impact of political factors on crime. The author examines the relation between greater electoral competition and homicide at the subnational level in a country undergoing an uneven transition to democracy. In societies characterized by the presence of patronage networks, social and political changes that undermine the source of unequal exchange between actors at different levels in the social hierarchy result in a temporary loss of social control and an increase in crime. The relation between electoral competition and homicide is tested using electoral results from a sample of 1,800 Mexican municipalities. Greater electoral competition is associated with higher homicide rates across municipalities and over time, even after controlling for standard correlates of violent crime. Consistent with the hypothesis that the increase is due to the disruption of patronage networks, this association is present only in rural areas where patron-client relations are more common.